2019
DOI: 10.1016/j.hpb.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of the long-term economic impact of major bile duct injury

Abstract: Background: Complications and litigation after bile duct injury (BDI) result in clinical and economic burden. The aim of this study was to comprehensively evaluate the long-term clinical and economic impact of major BDI. Method: Patients with long-term follow-up after Strasberg E BDI were identified. Costs of treatment and litigation were the primary outcome. Relationships between these outcomes and repair factors, like timing of repair and surgeon expertise, were secondary outcomes. Results: Among 139 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The primarily aims of surgical care are to save the patient's life, prevent the patient from further disease complications or reduce the risk of sustaining them, improve the patient's quality of life, and eliminate the possibility of iatrogenic injury associated with surgery. Gallbladder surgery for benign biliary disease is an excellent example of this concept because injury to any classified bile duct is considered avoidable [14][15][16]. This paper highlights the decision-making during and the technical details of gallbladder surgery related to double conversion in an acute surgery setting with atypical gallbladder anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The primarily aims of surgical care are to save the patient's life, prevent the patient from further disease complications or reduce the risk of sustaining them, improve the patient's quality of life, and eliminate the possibility of iatrogenic injury associated with surgery. Gallbladder surgery for benign biliary disease is an excellent example of this concept because injury to any classified bile duct is considered avoidable [14][15][16]. This paper highlights the decision-making during and the technical details of gallbladder surgery related to double conversion in an acute surgery setting with atypical gallbladder anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…34,38 Two systematic reviews, one published in 2013 by Landman et al and another currently in press by Halle-Smith and colleagues concluded that given the current available evidence, it is difficult to make any conclusions about the influence of BDI on HRQoL. 40,41 The Landman paper, after controlling for length of follow-up, found there was no difference between matched BDI and uneventful LC patients in the physical composite HRQoL score. 40 However, BDI patients were 38 times more likely to have a decreased mental composite score and this reduced score did not seem to improve over time.…”
Section: Perspectivementioning
confidence: 99%
“…Halle-Smith et al concluded that the effect of BDI on HRQoL remains unclear, but that it is possibly related to the severity of the injury and whether a surgical repair was performed, a conclusion that seems plausible despite several studies that conclude the contrary. 41 There are several factors that can be attributed to the absence of analyses of large patient cohorts in the form of meta-analyses, that make comprehensive investigation challenging for this important and relevant topic. No diseasespecific HRQoL survey tool for patients with BDI exists, and although the SF-36 and Gastrointestinal QoL (GiQLi) surveys are the most commonly used, there is a significant degree of variability in HRQoL surveys used between studies.…”
Section: Perspectivementioning
confidence: 99%
“…Also, it’s well established the importance of the surgeon’s experience and formal Hepatobiliary and pancreatic (HPB) training when treating bile duct injuries. As Halle-Smith et al described, reconstruction performed by a non-hepatobiliary surgeon increases a 4-time risk to present postoperative complications 14 . Among those relevant factors, time of reconstruction rises in literature as a key component of reduced morbidity and mortality 21 .…”
Section: Introductionmentioning
confidence: 99%